2020
DOI: 10.1093/jbcr/iraa020
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of High Vs Standard Daptomycin Doses Examined in Chinese Patients With Severe Burn Injuries by Pharmacokinetic Evaluation

Abstract: Previous studies and the concentration-dependent antibacterial actions of daptomycin suggested that a high dose would be needed for difficult-to-treat infections in burn patients. Here, we evaluated the effects of administration of low and high doses of daptomycin in patients with severe burn injuries. The study retrospectively analyzed 10 patients with severe burn injuries, using pharmacokinetic (PK) and pharmacodynamic (PD) evaluations of daptomycin doses given to combat serious infections. Daptomycin was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…To the best knowledge, we are the first to determine the daptomycin concentration in LVAD recipients. We observed a serum peak, reached after one hour, and gradually decreasing concentrations over the following 24 h. Our daptomycin serum concentration aligned with pharmacokinetic observations from previous clinical studies, including burn injuries and sepsis [29,47]. The typical serum pharmacokinetics of daptomycin have been observed already in previous studies and were confirmed by our serum findings [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…To the best knowledge, we are the first to determine the daptomycin concentration in LVAD recipients. We observed a serum peak, reached after one hour, and gradually decreasing concentrations over the following 24 h. Our daptomycin serum concentration aligned with pharmacokinetic observations from previous clinical studies, including burn injuries and sepsis [29,47]. The typical serum pharmacokinetics of daptomycin have been observed already in previous studies and were confirmed by our serum findings [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…The present evidence does not reflect true high-dose daptomycin because these high doses are used to achieve concentrations comparable to standard doses. Indeed, the steady-state AUCs achieved from 12 mg/kg/24-hours in this study reached exposure similar to 6 mg/kg/d in healthy volunteers (642 former 109 vs 632 latter 92 ). Whether doses >12 mg/kg would be beneficial in an MRSA bacteremia secondary to thermal burns to achieve the comparable 8- to 10-mg/kg dose remains undescribed.…”
Section: Special Populationssupporting
confidence: 59%
“…106,108 A 10-to 12-mg/kg/d dose may be prudent to achieve efficacy in burn patients; however, as burn wounds heal, daptomycin dosing may require reductions as clearance normalizes. Recently, Huang et al 109 retrospectively compared 10 patients receiving high-dose daptomycin 12 mg/ kg/d with 6 mg/kg/d. High-dose daptomycin had significantly higher peak concentrations than 6 mg/kg/d and a doubled AUC, with no difference in adverse events.…”
Section: Burnsmentioning
confidence: 99%
“…Interestingly, a higher dose of 4 mg/kg may be more effective in patients with cSSSI as daptomycin has a dose-dependent bactericidal action and 7 mg/kg may help both to maximize the bactericidal action and avoid the development of bacterial resistance [ 38 ]. A recent study of Chinese patients with severe burns and MRSA infection also found that high doses of daptomycin (from 6 mg/kg/day up to 12 mg/kg/day) were more effective than the standard dose [ 53 ]. Even if this dosage is higher than what is recommended, no significant differences of endogenous creatinine clearance rate (Ccr), blood urea nitrogen (BUN), and total protein (TP) were found in patients before and 7 days after high-dose daptomycin treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The mean concentration of albumin on day 7 after high-dose daptomycin treatment was significantly higher than the baseline value (40.5 ± 4.6 vs. 35.0 ± 6.5, respectively, p = 0.006). [ 53 ] We recommend that the physician should always assess the risk-benefit ratio in the individual patient before considering high doses of daptomycin.…”
Section: Resultsmentioning
confidence: 99%